The ambiguous role of NKX2-5 mutations in thyroid dysgenesis - Van Engelen, K; Mommersteeg, M; Baars, M; Lam, J; Ilgun, A; Van Trotsenburg, A; Smets, A; Christoffels, V; Mulder, B; Postma, A (Public Library of Science, 2012)
NKX2-5 is a homeodomain-containing transcription factor implied in both heart and thyroid development. Numerous mutations in NKX2-5 have been reported in individuals with congenital heart disease (CHD), but recently a select few have been associated with thyroid dysgenesis, among which the p.A119S variation. We sequenced NKX2-5 in 303 sporadic CHD patients and 38 families with at least two individuals with CHD. The p.A119S variation was identified in two unrelated patients: one was found in the proband of a family with four affected individuals with CHD and the other in a sporadic CHD patient. Clinical evaluation of heart and thyroid showed that the mutation did not segregate with CHD in the familial case, nor did any of the seven mutation carriers have thyroid abnormalities. We tested the functional consequences of the p.A119S variation in a cellular context by performing transactivation assays with promoters relevant for both heart and thyroid development in rat heart derived H10 cells and HELA cells. There was no difference between wildtype NKX2-5 and p.A119S NKX2-5 in activation of the investigated promoters in both cell lines. Additionally, we reviewed the current literature on the topic, showing that there is no clear evidence for a major pathogenic role of NKX2-5 mutations in thyroid dysgenesis. In conclusion, our study demonstrates that p.A119S does not cause CHD or TD and that it is a rare variation that behaves equal to wildtype NKX2-5. Furthermore, given the wealth of published evidence, we suggest that NKX2-5 mutations do not play a major pathogenic role in thyroid dysgenesis, and that genetic testing of NKX2-5 in TD is not warranted.